MENGATASI KEJENUHAN BELAJAR DARING MELALUI PENDEKATAN BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT PADA SISWA SMA 1 BAE - Rizal Mubaroq; Masturi Masturi; Santoso Santoso (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The objectives of this study are: 1) To determine the factors that cause students to experience online learning boredom. 2) To overcome students' online learning boredom by applying a behavioristic approach with self-management techniques for SMA 1 Bae students. The type of research used in this study is a qualitative research designed in the form of a case study. The subjects studied were TG and DS. The data collection techniques used were 1) interview, 2) observation, 3) documentation. The researcher used purposive sampling as a sample for the research subject of two students who had online learning boredom problems. Based on these results, it can be concluded that behavioristic counseling services with self-management techniques in overcoming the problem of online learning boredom are said to be very effective. In this case the researcher hopes that students can maintain the changed behavior.